2021
DOI: 10.1186/s12872-021-01975-x
|View full text |Cite
|
Sign up to set email alerts
|

Myocardial bridging presenting as myocardial ischaemia induced cardiac arrest: a case report

Abstract: Background Myocardial bridging is a congenital anomaly defined as a segment of epicardial coronary arteries running through the myocardium. Various complications related to myocardial bridging have been reported, but at present, cardiac arrest has rarely been reported. Case presentation We report one case of a patient who was successfully resuscitated from ventricular fibrillation cardiac arrest and was diagnosed with myocardial bridging accompanie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 22 publications
0
12
0
Order By: Relevance
“…Since most patients with MBs have no clinical symptoms, many clinicians are reluctant to manage it with intensive medical treatments then just tend to recommend simple observation with not much clinical significance. Although most cases with MBs are clinically benign ( 7 ), as suggested in the present case, sometimes it can be one of potential threats of MI and life-threatening arrhythmia ( 9 , 10 ). According to an observational retrospective study, MB seems to be a potential cause of MI, and its prevalence was significantly higher in patients with MINOCA than in their counterparts ( 10 ).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Since most patients with MBs have no clinical symptoms, many clinicians are reluctant to manage it with intensive medical treatments then just tend to recommend simple observation with not much clinical significance. Although most cases with MBs are clinically benign ( 7 ), as suggested in the present case, sometimes it can be one of potential threats of MI and life-threatening arrhythmia ( 9 , 10 ). According to an observational retrospective study, MB seems to be a potential cause of MI, and its prevalence was significantly higher in patients with MINOCA than in their counterparts ( 10 ).…”
Section: Discussionmentioning
confidence: 57%
“…In other words, MB may contribute to the development of acute coronary syndrome such as myocardial infarction (MI) or cardiac arrest ( 5 7 ). Especially, coronary vasospasm (CVS) may act as a trigger factor for these situations in patients with MB ( 7 ). We present a case of ST-segment elevation MI triggered by CVS within the site of MB.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, some researchers have considered MBs to be an independent risk factor for coronary atherosclerosis 6 . It has been reported that vasospasm caused by MBs may not only be the cause of myocardial ischemia and ventricular brillation and cardiac arrest but also lead to myocardial brosis, contractile band necrosis, and increased vascular density, which is closely related to myocardial insu ciency, angina pectoris, acute myocardial infarction and malignant arrhythmia 7,8 . Biomechanical changes caused by MBs are also the basis of its complications, such as plaque vulnerability, thrombosis, and vasospasm.…”
Section: Commentmentioning
confidence: 99%
“…On the other hand, the angiographic prevalence of MB was reported as 5% [18]. Although MB has been reported to be associated with acute coronary syndrome in many studies, no definite pathologic correlation between MB and acute coronary syndrome has been clearly established and it is generally considered a benign condition [19,20].…”
Section: Figure 2: Case Definitions Of Probable and Confirmed Myocard...mentioning
confidence: 99%